Phytoplankton dynamics in the North American Great Lakes - Munawar, M.; Munawar, Iftekhar Fatima (Ecovision world monograph series., 2014)
Phytoplankton Dynamics in the North American Great Lakes is the compilation of two volumes, originally published 1996 and 2000. Both volumes provide a thorough treatment of the community structure, function, and dynamics of phytoplankton in the North American Great Lakes and represent the culmination of nearly three decades' worth of work by Mohiuddin Munawar and Iftekhar F. Munawar. With these volumes, the phycology of the North American Great Lakes has been brought into the new millennium. Volume 1 focuses on the Lower Great Lakes-Lakes Ontario and Erie-while volume 2 highlights Lakes Mich.